The Bumiputra corporate strategies in Malaysian securities industry with special emphasis on the Bumiputra stock exchange / Abd. Raman Abu Samah - Abu Samah, Abd. Raman (1985)
The Malaysian Securities Industry is still relatively young as compared to that of developed countries like the United States, Japan and Great Britain. A Stock Exchange, therefore, has a crucial role to play in the capital formation so necessary for the growth of, and investment in the dynamic corporate sector. With the rapid growth of the corporate sector in Malaysia and thus the economy, there is a necessity to see that wealth is evenly distributed, where the Bumiputras are given a meaningful stake in the corporate sector to eliminate racial stereo-typing by occupation and economic functions. Hence, corporate restructuring along the lines of the New Economic Policy (NEP) poses new challenges to corporate planners. In the floatation of public companies, it becomes necessary to reserve a specified quota of new shares for Bumiputras and Bumiputra institutions. The Bumiputra Stock Exchange (BSE) was set up not to compete with the Kuala Lumpur Stock Exchange (KLSE) but merely to provide an alternative for the Bumiputra companies that are not qualified to be listed in the latter to participate in the stock market catering only for the Bumiputra investors. The Bumiputra companies listed on the BSE will be groomed and later when they are already successful, they may have the option to be promoted to the KLSE.